Preparation of the Antioxidant Compounds from the Styrene and P-Benzoquinone Compounds to the Lubricant Oils - Faez Sameer Salih - Raed Kadhim Zaidan _ Khansa Abdul Razzaq Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
In this study, new antioxidants were synthesized using (thiol-ene) click reaction where, octane and dodecane thiol were added to styrene which produced from plastic waste as (1:1) mole ratio at rate temperature to obtain the following antioxidant compounds: Octyl(2-phenylethyl) sulfane and Dodecyl(2-phenylethyl) sulfane respectively. Octane and dodecane thiol were also added to p-benzoquinone compound to obtain of the following antioxidant compounds, 2-(Octylthio) benzene-1,4-diol and 2-(Dodecylthio) benzene-1,4-diol respectively.    These synthesized antioxidants were added to the lubricating oils such as, engine and hydraulic oils with base oil as a solvent, and then mixed well. Then the characterization of these synthesized antioxidant compounds were specified by using techniques such as, (FT-IR), (NMR) and mass spectroscopy. Then study their efficacy as an antioxidant compounds by using of (FT-IR) and (cyclic voltammetry) techniques.